PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Nuzulul Qurnain; Gazali Gazali (Al-Amien Prenduan for Islamic Institute, 2021)
Today's culinary world is growing very rapidly, making competition between culinary companies increasingly fierce. So that companies must pay attention to their employees so that employees work optimally and have a high organizational commitment to the company. With high organizational commitment, employees will not easily leave the company, this is an advantage for the company because it reduces recruitment costs. For this reason, the company must have a strong organizational culture and continuously improve employee job satisfaction. Data collection was done by using a questionnaire. This study uses a saturated sample because all the population is sampled. Saturated sampling is a technique of determining the sample when all members of the population are used as samples. The unit of analysis used in this study is the employee at Asela Restaurant. Namely as many as 64 employees who will be the sample in this study. Data analysis in this study was carried out with 2 types of analysis, namely Descriptive Statistical Analysis and Multiple Linear Regression Analysis using the SPSS program. The result of this research is that the first is that organizational culture has a significant effect on employee performance, and the second is that job satisfaction has a significant effect on employee performance.